Tinjauan Hukum tentang Larangan Calon Anggota Dewan Perwakilan Daerah Berasal dari Pengurus Partai Politik Pasca Putusan Mahkamah Konstitusi NO.30/PUU-XV/2018 - Muh Saldi; Muin Fahmal; Agussalim A Gadjong (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract: This study aims to find out how the basic considerations of the Constitutional Court in Establishing the Prohibition of Candidates for Members of the RegionalRepresentative Council come from Political Party Management and What are the Implications of the Prohibition of Political Party Managers from becoming Members of the Regional Representative Council within the framework of a democratic legal state This thesis research uses a normative legal research type, which is based on laws and regulations that use primary legal materials that have binding power as the main basis in this research, including the 1945 Constitution of the Republic of Indonesia and other related regulations. Secondary materials, namely materials that are closely related to primary legal materials and help analyze and understand primary legal materials, such as the results of previous research related to Constitutional Court Decisions. The results of this study indicate that the basic considerations of the Constitutional Court in Establishing the Prohibition of Candidates for Members of the Regional Representatives Council from the Political Party Management are based on Philosophical, Juridical and Sociological Foundations. This is based on the original intent of the formation of the DPD as regional representation reflecting the existence of groups in the region. the community is represented by figures who are members of the DPD so that it is hoped that there will be no double representation. As for the implication of the prohibition of political party administrators from becoming members of the Regional Representatives Council within the framework of a democratic legal state, it is stated that the nomination of DPD members may not come from political party administrators in the general election which then has an impact on the presence of decisions that do not go hand in hand as if they will be contradictory. Abstrak: Penelitian bertujuan untuk mengetahui Bagaimana dasar Pertimbangan Mahkamah Konstitusi dalam Menetapkan Larangan Calon Anggota Dewan Perwakilan Daerah berasal dari Pengurus Partai Politik Dan Bagaimana Implikasi Larangan Pengurus Partai Politik untuk menjadi Anggota Dewan Perwakilan Daerah dalam kerangka negara hukum Demokratis. Penelitian skripsi ini menggunakan tipe penelitian hukum normatif, yang disandarkan pada peraturan Perundang undangan yang menggunakan bahan hukum primer yang mempunyai kekuatan mengikat sebagai landasan utama dalam penelitian ini, diantaranya Undang – undang Dasar Negara Republik Indonesia Tahun 1945 dan peraturan terkait lainnya. Bahan sekunder, yaitu bahan-bahan yang erat hubungannya dengan bahan hukum primer dan membantu menganilisis dan memahami bahan hukum primer, seperti hasil penelitian sebelumnya yang berkaitan dengan Putusan Mahkamah Konstitusi. Hasil Penelitian ini menunjukkan bahwa dasar pertimbangan Mahkamah Konstitusi dalam Menetapkan Larangan Calon Anggota Dewan Perwakilan Daerah berasal dari Pengurus Partai Politik disandarkan pada Landasan Filosofis, Yuridis dan Sosiologis.. Hal tersebut didasari pada original intent dari pembentukan DPD sebagai representasi daerah mencerminkan keberadaan golongan-golongan di masyarakat diwakili para tokoh yang menjadi anggota DPD sehingga diharapkan tidak terjadinya double representation. Adapun Implikasi Larangan Pengurus Partai Politik untuk menjadi Anggota Dewan Perwakilan Daerah dalam kerangka negara hukum Demokratis membawa ketentuan pencalonan anggota DPD tidak boleh berasal dari pengurus partai politik pada pemilihan umum yang kemudian berdampak pada hadirnya putusan yang tidak berjalan beriringan seakan akan bertolak belakang.